Privacy with Delegation of Rights by Identity Management - Wohlgemuth, Sven; Müller, Günter (Emerging Trends in Information and Communication Security, 2006)
Privacy in business processes with proxies is not possible. Users need to share attributes with their proxies which leads to “Big Brothers”. This is the reason why identity management systems such as Liberty Alliance and Microsoft .NET Passport are not successful. We propose a generic privacy-preserving protocol for sharing identifying attributes as credentials with others. This delegation protocol extends current identity management systems.